Auditing : an assertions approach - Taylor, Donald H.; Glezen, G. William (New York : John Wiley and Sons, 1997)
This book is about: The audit function; The public accounting profession and auditing standards; The Auditor's ethical environment; ...
Keywords: Economics; Auditing; Sampling (Statistics); Auditing; Auditing -- Data processing